Sulfur and Azobenzenes, a Profitable Liaison: Straightforward Synthesis of Photoswitchable Thioglycosides with Tunable Properties. Issue 39 (1st June 2022) - Berry, Jonathan; Lindhorst, Thisbe K.; Despras, Guillaume
Abstract: Azobenzene photoswitches are valuable tools for controlling properties of molecular systems with light. We have been investigating azobenzene glycoconjugates to probe carbohydrate‐protein interactions and to design glycoazobenzene macrocycles with chiroptical and physicochemical properties modulated by light irradiation. To date, direct conjugation of glycosides to azobenzenes was performed by reactions providing target compounds in limited yields. We therefore sought a more effective and reliable coupling method. In this paper, we report on a straightforward thioarylation of azobenzene derivatives with glycosyl thiols as well as other thiols, thereby increasing the scope of azobenzene conjugation. Even challenging unsymmetrical conjugates can be achieved in good yields via sequential or one‐pot procedures. Importantly, red‐shifted azoswitches, which are addressed with visible light, were easily functionalized. Additionally, by oxidation of the sulfide bridge to the respective sulfones, both the photochromic and the thermal relaxation properties of the core azobenzene can be tuned. Utilizing this option, we realized orthogonal three‐state photoswitching in mixtures containing two distinct azobenzene thioglycosides. Abstract : Tunable properties : A direct thioarylation of azobenzenes allows to obtain symmetrical as well as challenging unsymmetrical conjugates in good yields. Importantly, photochromic and thermal relaxation properties can be easily tuned via oxidation of the sulfide linkage.